A single-center experience on percutaneously performed partial omentectomy in pediatric peritoneal dialysis patients. (June 2014) - Aksu, Nejat; Alparslan, Caner; Yavascan, Onder; Bal, Alkan; Erdogan, Hakan; Kara, Orhan Deniz; Kasap Demir, Belde; Saritas, Serdar; Elmas, Cengiz Han; Senturk, Sevginar
Abstract Objective: This study describes a single-center experience on percutaneously performed partial omentectomy procedure in pediatric peritoneal dialysis (PD) patients who showed early catheter dysfunction and required catheter replacement due to catheter flow obstruction. Materials and methods: We performed a retrospective review of clinical outcomes from pediatric PD patients who underwent percutaneous catheter replacement by pediatric nephrologists between November 1995 and December 2012. Partial omentectomy was performed in those patients in whom omental or adhesion trapping to the catheter tip was seen. Results: During the study period, catheter dysfunction that eventually required percutaneous catheter replacement occurred in 32 (23.7%) children. Of these, 9 patients were performed partial omentectomy. Mean age at initiation of PD and time of omentectomy was 97.48 ± 46.06 and 98.53 ± 45.55 months, respectively. Catheter dysfunction appeared after a mean 1.20 ± 1.0 months. The causes of catheter dysfunction were omental wrapping and malposition. No peritonitis occurred before omentectomy. Mean total operation time was 60 ± 8.83 min. No complications were encountered during the procedure. After omentectomy, mean catheter survival period was 5.92 ± 6.88 months. A total of five peritonitis episodes occurred. Three patients were transferred to hemodialysis. Six patients were on PD treatment without any problem at the end of the first year of their follow-up. Two patients underwent kidney transplantation. Four patients were still on chronic PD treatment at the end of the study period. Conclusion: When performed by an experienced nephrologist, the performance of partial omentectomy by percutaneous route, when required, is an easy, safe and efficient therapeutic procedure in children on chronic PD treatment.